2018
DOI: 10.1016/j.amjsurg.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy and intraoperative enteroscopy for obscure gastrointestinal bleeding before and after the era of video capsule endoscopy and deep enteroscopy: A tertiary center experience

Abstract: Background To evaluate roles of intraoperative endoscopy (IOE) in management of severe obscure GI bleeding (OGIB) before vs. after introduction of video capsule endoscopy (VCE) and deep enteroscopy (DE). Methods We retrospectively reviewed prospectively collected data of patients undergoing IOE for severe OGIB in a tertiary referral center. Results 52 patients had laparotomy/IOE for OGIB, 11 pre and 41 post VCE/DE eras. In the pre VCE/DE era, 36.4% (4/11) had preoperative presumptive diagnoses while in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The most common route of IOE was transoral followed by trans-enterotomy. A recent study by Manatsathit W, et al also reported vascular lesions, ulcers and tumors to be the most common lesions detected on IOE [36].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The most common route of IOE was transoral followed by trans-enterotomy. A recent study by Manatsathit W, et al also reported vascular lesions, ulcers and tumors to be the most common lesions detected on IOE [36].…”
Section: Discussionmentioning
confidence: 91%
“…The reported rates of diagnostic and therapeutic yield of IOE are 79.3% (58-100%) and 75.7% (48-94%), respectively [1-10, 16, 36]. The diagnostic yield for obscure GI bleeding after non-diagnostic abdominal imaging has been reported to be 91-100% and after non-diagnostic VCE/DAE varies from 14.2% to 66.7% [1,6,9,36]. Traditionally, the treatment of the lesions detected during IOE were performed surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this could explain the high rate of surgery in adults who were not screened at a young age. 23 In our centre, 64% of PJS patients had undergone SB surgery before joining the screening programme. Third, with the mastery of SBP endoscopic polypectomy over the past decade at our centre, more challenging resections of large/difficult polyps were successfully attempted.…”
Section: Discussionmentioning
confidence: 97%
“…Concerning IOE, it has been described as a valuable tool in patients with tumours, Meckel's diverticulum 23 and Obscure gastrointestinal bleeding (OGIB), finding a bleeding source in about 80% of cases. 24 In addition, Edwards et al described how this technique improves polyp clearance without the need for additional enterotomies and may help to reduce the frequency of laparotomies in PJS.…”
Section: Discussionmentioning
confidence: 99%